PALEOSHORELINE GEOMORPHOLOGY OF BööN TSAGAAN NUUR, TSAGAAN NUUR AND OROG NUUR: THE VALLEY OF LAKES, MONGOLIA - Komatsu G.; Brantingham P.J.; Olsen J.W.; Baker V.R. (My University, 2001)
We conducted a preliminary study of paleoshoreline features associated with Böön Tsagaan Nuur, Tsagaan Nuur, and Orog Nuur, lakes located in the Gobi–Altai transition zone of the Valley of Lakes (Dolina Ozor) which stretches from central to western Mongolia. The paleoshoreline features were first identified on RADARSAT satellite SAR imagery. We investigated the features during the 1998 field season of the Joint Mongolian–Russian–American Archaeological Expedition to the Gobi–Altai region. We identified paleoshorelines of multiple elevations in the field, which are considered to be relict beach ridges and wave-cut terraces. Other paleolake landforms include spits and Gilbert-type deltas. These landforms are complex, large and well established, implying that the paleolakes were stable for extended periods. The reconstructed paleolakes cover extensive areas of the valley floor, implying that hydrological and climatic conditions were very different in the past. Paleolake expansions may have occurred under a variety of circumstances. One hypothesis is that the high lake stands occurred during the wetter period corresponding to the Oxygen Isotope Stage 3 prior to the Last Glacial Maximum (LGM), during the warmest early Holocene and the late Holocene, or during all these periods. If low evaporation rates due to lower temperatures, glacier meltwater and possibly increased precipitation are important factors, then the expansions may have occurred during the terminal Late Glacial period after the Last Glacial Maximum. The greatly expanded lakes in the Gobi–Altai could have significantly affected the Quaternary human demography and migration in the region.
Keywords: Holocene; Quaternary; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная